Prediction Retweet Using User-Based and Content-Based with ANN-GA Classification Method - Edvan Tazul Arifin; Jondri Jondri; Indwiarti Indwiarti (Building of Informatics, Technology and Science (BITS), 2022)
Current technological advances have caused rapid dissemination of information, especially on social media, one of which is Twitter. Retweeting or reposting messages is considered an easily available information diffusion mechanism provided by Twitter. By finding out why a user retweets a tweet from another person and by making this prediction we can understand how information diffuses on Twitter. In this study, Artificial Neural Network – Genetic Algorithm is used in the classification process and uses user-based and Content-Based features. Evaluation result obtained in this study are 90% accuracy, 72% precision, 83% recall, and 65% F1-Score value on the model by Oversampling.